2014
DOI: 10.5897/jpvb2014.0176
|View full text |Cite
|
Sign up to set email alerts
|

Altered total cholesterol and triglyceride levels during the course of Plasmodium falciparum infection in children

Abstract: Changes of lipid parameter concentrations are observed in patients suffering from malaria. However, there are few data on their evolution during the course of the infection and their relationship with the infection parameters. The levels of triglycerides (TG) and total cholesterol (TC) were measured during and after uncomplicated Plasmodium falciparum malaria in 122 children. The relationship with the antimalarial drug treatment, the parasite density and haemoglobin levels was also assessed. Mean TG levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…The other hypothesis is that TG is derived from the phospholipids of RBC membrane following hemolysis and hypertriglyceridemia is described in disease with hemophagocytosis although not investigated. 48 In contrast to our study, a study in Nigeria showed that TC and TG cholesterols of malaria-infected patients and controls showed no significant differences but were similar to our findings of serum LDL and HDL (P< 0.05) of malariainfected patients, which were below reference intervals. 49,50 The decreased HDL might be due to reduction in the transport of cholesterol, esterification by lecithin cholesterol acyl transferase, and inhibition of liver enzyme by a parasite factor.…”
contrasting
confidence: 56%
“…The other hypothesis is that TG is derived from the phospholipids of RBC membrane following hemolysis and hypertriglyceridemia is described in disease with hemophagocytosis although not investigated. 48 In contrast to our study, a study in Nigeria showed that TC and TG cholesterols of malaria-infected patients and controls showed no significant differences but were similar to our findings of serum LDL and HDL (P< 0.05) of malariainfected patients, which were below reference intervals. 49,50 The decreased HDL might be due to reduction in the transport of cholesterol, esterification by lecithin cholesterol acyl transferase, and inhibition of liver enzyme by a parasite factor.…”
contrasting
confidence: 56%
“…In contrast to cholesterol, hypertriglyceridemia was observed in plasma. Our observation of increased plasma TAG in malaria patients agrees with the observation of other researchers [32,33]. The observed parasite-induced plasma hypertriacylglycerolemia in this study could be the result of either elevated VLDL biosynthesis or reduced VLDL elimination [34].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance, previous studies and a recent metaanalysis showed congruent lipid profile changes during malaria infection. [2][3][4][5]7,8,10,11,13,14,24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] The meta-analysis (2013) was updated with the data of the present study, further strengthening the findings of that study. 7 The extent of these serum lipid profile changes was not related to parasitemia, in contrast to three other studies.…”
Section: Discussionmentioning
confidence: 63%